The effects of obesity and insulin dysregulation on mare reproduction, pregnancy, and foal health: a review - Hallman, Isa; Karikoski, Ninja; Kareskoski, Maria (Frontiers in Veterinary Science, 2023)
Obesity is a growing welfare concern in modern equine populations and predisposes horses to disturbances in energy metabolism such as insulin dysregulation. However, equine metabolic syndrome has only been recognized in recent decades. Functioning energy metabolism is pivotal to normal body homeostasis and affects essentially all organ systems, including reproduction. Previous literature suggests that obesity has an effect not only on the reproductive processes in mares but also on offspring health, predisposing the offspring to later-onset orthopedic and metabolic problems. This review focuses on the effects of obesity, insulin dysregulation and hyperinsulinemia on the reproductive functions of mares and the implications on foal health before and after birth. The points of interest are the cyclicity and ovarian function, uterine environment, gestation, the postpartum period, and the newborn foal. The aim is to review the current state of knowledge, and identify outstanding questions that could stimulate future research. This topic is important not only from the equine industry and production perspective but is also relevant for the welfare of future populations and individuals.